Cronobacter sakazakii: stress survival and virulence potential in an opportunistic foodborne pathogen - Feeney, Audrey (Gut Microbes, 2015)
A characteristic feature of the opportunistic foodborne pathogen Cronobacter sakazakii is its ability to survive in extremely arid environments, such as powdered infant formula, making it a dangerous opportunistic pathogen of individuals of all age groups, especially infants and neonates. Herein, we provide a brief overview of the pathogen; clinical manifestations, environmental reservoirs and our current understanding of stress response mechanisms and virulence factors which allow it to cause disease.